The ’Aha’ Moment: Exploring autism narratives as told by the mothers of autistic girls - Evans, Mairi (Murmurations: Journal of Transformative Systemic Practice, 2022)
Research highlights increasing awareness that autism can present differently in girls, and that girls in the UK wait longer to be identified, referred, and diagnosed in comparison to their male counterparts. Whilst there is a growing body of research about girls, and the experience of mothering an autistic girl, less is known about the impact of the diagnosis itself. This article explore the history of autism diagnosis, autism and girls and introduces my doctoral study, conducted from a social constructionist viewpoint, exploring the diagnostic journey of 12 mothers in the UK to identify the meanings attributed to their daughter’s diagnosis.